Weight Loss Percentage Prediction of Subsequent Neonatal Hyperbilirubinemia in Exclusively Breastfed Neonates - Rui-Jane Chang; Hung-Chieh Chou; Yu-Hsun Chang; Mei-Huei Chen; Chien-Yi Chen; Wu-Shiun Hsieh; Po-Nien Tsao (Pediatrics and Neonatology)
The incidence of neonatal hyperbilirubinemia in our hospital has increased since the implementation of breastfeeding promotion. Inadequate breastfeeding results in reduced calorie intake, weight loss and neonatal hyperbilirubinemia. Supplementary feeding is required if breastfeeding proves inadequate. However, the optimal weight loss cut-off value for supplementary feeding is unknown. Methods: We collected records for all healthy neonates with a gestational age ≥35 weeks and birth body weight (BBW) above 2500 g, born between March 2002 and July 2005, from our nursery. A total of 1979 neonates were reviewed, 874 of whom were exclusively breastfed and subsequently enrolled in this study. Only infants who were breastfed exclusively were enrolled; 219 of these infants (25.1%) presented significant hyperbilirubinemia after 72 hours of age. Infants with early-onset (<48 hours) hyperbilirubinemia or any known risk factors for neonatal hyperbilirubinemia were excluded. We analyzed the association between weight loss percentage and hyperbilirubinemia and investigated the best weight loss percentage cut-off value for the prediction of subsequent hyperbilirubinemia before 2 weeks of age. Results: Neonates with lower gestational age and greater weight loss percentage were associated with hyperbilirubinemia. By using weight loss ≥8% of BBW after 48 hours and weight loss ≥11% of BBW after 72 hours as the cut-off values for the prediction of subsequent hyperbilirubinemia, negative predictive values were 77.7% and 76.8%, respectively. Conclusion: This study documented the relationship between weight loss percentage and subsequent hyperbilirubinemia incidence. Our data provide a basis for determination of an optimal weight loss percentage cut-off value that indicates supplementary feeding.